Using Feedback in Teaching Writing Descriptive Text - Nada Raudhotul Muthoharoh; Anita Anita (English Education Department, 2018)
This study is to see the improvement of student’s writing skill on descriptive text for seventh grade students of SMP 14 Kota Serang by using peer feedback technique. The subject of this research is the students of seventh grade of SMP 14 Kota Serang which consist of 30 students. This research is applied by a quasi-experimental design and quantitative research method. The instrument used in this research was tests (pre-test and post-test) which is conducted based on the main problems: 1) How is the students writing ability on descriptive text at the seventh grade of SMP 14 Kota serang? 2) How is the effectiveness of peer feedback in teaching writing descriptive text at the seventh grade of SMP 14 Kota serang?. The research finding of the last result showed that “to” from the calculation is higher than t table both at significance level 5% and 1%. Significance 5% t observation= 7.14 and t table= 1.67 or 7.14 >1.67 which its significance 1% t observation=7.14 and t table= 2.39 or 7.14 >2.39. In addition, the result of observations showed that the students more motivated in learning English, especially for writing subject. Based on the result above, it can be concluded that peer feedback can be used in teaching writing descriptive text. The result of this research shows that the students’ writing on descriptive text who use peer feedback achieve better performance than those who do not use it.